2023
DOI: 10.12998/wjcc.v11.i11.2396
|View full text |Cite
|
Sign up to set email alerts
|

Platelet rich fibrin is not a barrier membrane! Or is it?

Abstract: Platelet-rich fibrin (PRF) is widely used in dentistry and other fields of medicine, and its use has become popular in dental implantology. In several published studies, PRF has been used as a barrier membrane. A barrier membrane is a sheet of a certain material that acts as a biological and mechanical barrier against the invasion of cells that are not involved in bone formation, such as epithelial cells. Among the basic requirements of a 'barrier membrane, occlusivity, stiffness, and space maintenance are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 46 publications
(53 reference statements)
0
18
0
Order By: Relevance
“…Reports have shown that GTR has been implemented as an adjunct to radicular cyst enucleation and apicoectomy for enhancement of periapical tissue healing, prevention of soft tissue collapse, and improvement of treatment outcomes[ 11 , 16 , 17 ]. Full recovery of the area around the apex of a tooth includes the regeneration of alveolar bone, periodontal ligament cells and cementum.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reports have shown that GTR has been implemented as an adjunct to radicular cyst enucleation and apicoectomy for enhancement of periapical tissue healing, prevention of soft tissue collapse, and improvement of treatment outcomes[ 11 , 16 , 17 ]. Full recovery of the area around the apex of a tooth includes the regeneration of alveolar bone, periodontal ligament cells and cementum.…”
Section: Discussionmentioning
confidence: 99%
“…GTR is a technique that uses a bone substitute material along with a membrane that serves both as a biological and physical shield to prevent cells that do not contribute to bone growth, such as epithelial cells, from invading the area. Moreover, GTR allows the migration of bone-forming cells from slow migration to bad sites, thereby ensuring selective cell re-population and guiding the proliferation of various tissues during the healing process[ 17 , 18 ]. Numerous studies have described this technique, with respect to the application of a wide range of materials and treatment protocols, all of which achieved clinical effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations